Acupuncture Treatment for 98 Cases of Ventricular Premature Beat - 韩宝杰 王锋 王新中（译） (Journal of traditional Chinese medicine, 2008)
Ventricular premature beat is a commonly encountered arrhythmia, which can occur in patients with and without cardiac diseases. In TCM, ventricular premature beat falls into the category of palpitation and obstruction of qi in the chest. The authors treated it with acupuncture and obtained satisfactory thera- peutic effects. A summary follows.